Uso de cinzas de carvão mineral da termelétrica do Pecém como material de cobertura seca de depósitos de resíduos - Souza, Henrique Petisco de (2018)
The use of residues from the burning of coal is a relevant issue in the present day, due to the significant amount of ash generated after the combustion process. In the state of Ceará, part of the energy generation is obtained by burning of coal, at the Pecém Energia Thermal Power Plant, located in the municipality of São Gonçalo do Amarante. The ashes generated in this thermoelectric are currently stored in containment basins, and it is necessary to propose alternatives of destination of this residue. The present work had as objective to study the application of ashes of mineral coal and of mixtures of soil and ash, in different proportions, as waterproofing material of dry landfill cover of urban solid waste. The work was divided into three stages: (a) determination of the hydraulic parameters of the materials used, (b) numerical modeling of the water balance of hedges, using Vadose software (GeoStudio, 2007) and (c) infiltration tests in laboratory lysimeters. In all, five numerical models of coverage, being four compounds with a waterproofing layer of 30 cm, with different soil-gray mixtures, which underlies an upper layer of protection 30 cm, and a model composed only of a soil layer, representing the conditions found in the landfill located in the municipality of Caucaia-CE, which receives the waste solids of the city of Fortaleza. The experimental models were constructed and reproduced three coverage configurations: (a) with the best soil-ash blend numerical modeling (with 70% of soil and 30% of ashes), instrumented with moisture sensors (b) with ash in its pure state and (c) and only with soil, represented the configuration of the sanitary landfill studied. In the columns, of infiltration, collecting the volume of percolated water. The results of the physical and demonstrated that the mixture with 70% of soil and 30% of ash has the potential to coverages, as it presented the lowest values ​​of percolation in relation to the precipitate volume, in addition to maintaining high saturation values ​​above 85%. THE ash in its pure state showed high values ​​of percolation and large variations in saturation conditions, a behavior similar to that observed for the covering the landfill in question.